Ternary Blended Cement Concrete Utilizing Rice Husk Ash And Ground Granulated Blast-Furnace Slag As Cement Replacement - Norbert, Bob Harris (2018)
Concrete is the most used materials in the world, in most part of the world, shelters are made of concrete. As the population growth increases every year, the need for shelter will consequently increase with the demand of concrete. Cement is an important material in concrete, it acts as the main binder. Cement manufacturing industries contributes up to 6-8% of the global carbon dioxide emission as well as energy intensive process and depletes our natural resources. Due to the harmful effects to our environment, hence the need to reduce the usage of cement is crucial. In this research, the materials, rice husk ash (RHA) and ground granulated blast-furnace slag (GGBS) were used in concrete as a cement replacement.